Laos’s Current Commitment to Tackle Deforestation: Gaps and Prospects in REDD+ Implementation - Estafetta Chrysantina Murakabhi; Septyanto Galan Prakoso; Hasna Dherin Syakira; Rahma Sintya Devi; Ihya Pradnya Sayoga (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2026)
Abstract Deforestation in Laos presents a critical environmental challenge with significant implications for biodiversity, climate change, and the socio-economic well-being of local communities. The main drivers of deforestation include shifting agriculture, illegal logging, and the conversion of forests into agricultural plantations, particularly for cassava and rubber. Despite Laos' efforts to address this issue through initiatives such as the REDD+ program and sustainable forest management strategies, challenges persist due to weak governance, limited local capacity, and economic dependence on forest resources. This paper explores the multifaceted causes of deforestation in Laos and evaluates the effectiveness of current measures to mitigate its impacts. Drawing on Green Political Theory, the study emphasizes the moral imperative of prioritizing ecological conservation over short-term economic gains. It also highlights the socio-economic consequences of deforestation, including habitat loss, decreased biodiversity, and conflicts over land rights. The findings suggest that while programs like REDD+ have potential, their success requires stronger enforcement mechanisms, inclusive policy frameworks, and active community involvement. By addressing these gaps, Laos can advance sustainable forest management and contribute to global efforts to preserve the environment. This study recommends improving policy implementation and fostering international collaboration to effectively tackle deforestation. Keywords: Deforestation in Laos, Green Political Theory, REDD+ Implementation Abstrak Deforestasi di Laos merupakan tantangan lingkungan yang kritis dengan implikasi signifikan bagi keanekaragaman hayati, perubahan iklim, dan kesejahteraan sosial-ekonomi komunitas lokal. Faktor utama penyebab deforestasi meliputi pertanian berpindah, penebangan liar, dan konversi hutan menjadi perkebunan pertanian, terutama untuk singkong dan karet. Meskipun Laos telah berusaha mengatasi masalah ini melalui inisiatif seperti Program REDD+ dan strategi pengelolaan hutan berkelanjutan, tantangan tetap ada akibat tata kelola yang lemah, kapasitas lokal yang terbatas, dan ketergantungan ekonomi pada sumber daya hutan. Artikel ini mengeksplorasi penyebab multifaset deforestasi di Laos dan mengevaluasi efektivitas langkah-langkah saat ini untuk mengurangi dampaknya. Dengan mengacu pada Teori Politik Hijau, studi ini menekankan kewajiban moral untuk memprioritaskan konservasi ekologi daripada keuntungan ekonomi jangka pendek. Studi ini juga menyoroti konsekuensi sosial-ekonomi deforestasi, termasuk hilangnya habitat, penurunan keanekaragaman hayati, dan konflik hak atas tanah. Temuan menunjukkan bahwa meskipun program seperti REDD+ memiliki potensi, keberhasilannya memerlukan mekanisme penegakan hukum yang lebih kuat, kerangka kebijakan yang inklusif, dan partisipasi aktif komunitas. Dengan mengatasi celah-celah ini, Laos dapat maju menuju pengelolaan hutan berkelanjutan dan berkontribusi pada upaya pelestarian lingkungan global. Studi ini merekomendasikan perbaikan implementasi kebijakan dan peningkatan kolaborasi internasional untuk mengatasi deforestasi secara efektif. Kata kunci: Deforestasi di Laos, Green Political Theory, Implementasi REDD+